2019
DOI: 10.4081/ejh.2019.3050
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of TLR4, MyD88, IRAK4 and NF-κΒ in the oviduct of Chinese brown frog (Rana dybowskii)

Abstract: One special physiological phenomenon of the Chinese brown frog (Rana dybowskii) is that its oviduct goes through expansion prior to pre-hibernation instead of expanding during the breeding period. Our previous study discovered that some cytokines such as interleukin-1 beta (IL-1β) and its receptor type I (IL1R1) proteins were expressed in the oviduct of Rana dybowskii. In this study, we continued to investigate the localizations and expression levels of cytokines including toll-like receptor 4 (TLR4) and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…When the IKK complex is activated, the phosphorylation of IKK causes the phosphorylation and degradation of IκB-α; then, NF-κB is released and translocated to the nucleus, is phosphorylated by nuclear kinases, and leads to the transcriptions of the immune-related gene. 40 To investigate whether the NF-κB signaling pathway also participated in macrophage activation by PSPP-1, we further studied the expressions of key proteins or their phosphorylated proteins by western blot. The results showed that PSPP-1 nearly unchanged the expressions of IKKα/β but activated the degradation of IκB-α and increased the phosphorylation of IKKα/β and IκB-α in RAW264.7 cells, which were significantly different in comparison to the control group (P < 0.05).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the IKK complex is activated, the phosphorylation of IKK causes the phosphorylation and degradation of IκB-α; then, NF-κB is released and translocated to the nucleus, is phosphorylated by nuclear kinases, and leads to the transcriptions of the immune-related gene. 40 To investigate whether the NF-κB signaling pathway also participated in macrophage activation by PSPP-1, we further studied the expressions of key proteins or their phosphorylated proteins by western blot. The results showed that PSPP-1 nearly unchanged the expressions of IKKα/β but activated the degradation of IκB-α and increased the phosphorylation of IKKα/β and IκB-α in RAW264.7 cells, which were significantly different in comparison to the control group (P < 0.05).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally, NF-κB is inactive and retained in the cytoplasm by specific inhibitor IκB-α, and the IKK complex (IKK α and IKK β) is a critical regulatory protein for the phosphorylation of IκBs. When the IKK complex is activated, the phosphorylation of IKK causes the phosphorylation and degradation of IκB-α; then, NF-κB is released and translocated to the nucleus, is phosphorylated by nuclear kinases, and leads to the transcriptions of the immune-related gene …”
Section: Results and Discussionmentioning
confidence: 99%
“…The activation of NF-κB (p65) requires IκBα phosphorylation. When activated p65 enters the nucleus and is phosphorylated (p-p65) by nuclear kinase, it induces the transcription of immune-related genes, promotes cytokine production, and enhances the innate and adaptive immunity [ 43 ]. PI3K is a lipid kinase that regulates key physiological and pathological cellular activities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with our previous studies. 2 , 31 , 33 , 34 However, in studies on the Argentine shortfin squid, it has been found that the reproductive organs (ovary and oviduct) account for an increasing proportion of energy during sexual maturation, building up energy for reproduction. 38 Different from non-breeding, the weight and length of the oviduct in guinea hens ( Numida meleagris ) displayed increased values during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 The dried product of the dilated oviduct, known as Oviductus Ranae , is widely used in traditional Chinese medicine due to its nourishing properties for Yin, lung moisture, and kidney essence replenishment. 33 , 34 Oviductus Ranae contains a variety of nutrients, with proteins and lipids being the most significant components, with lipid content of up to 50%. 34 …”
Section: Introductionmentioning
confidence: 99%